Seismic-Hazard Maps for Alaska and the Aleutian Islands: 3HZ050 - Wesson, Robert L.; Frankel, Arthur D.; Mueller, Charles S.; Harmsen, Stephen C.; Rukstales, Kenneth S. (compiler) (USGS Science Data Catalog, 1999)
Probabilistic seismic hazard maps were prepared for Alaska portrayingpeak horizontal ground acceleration and horizontal spectral responseacceleration for 0.2, 0.3, and 1.0 second periods with probabilitiesof exceedance of 10% in 50 years and 2% in 50 years. This particulardata set is for horizontal spectral response acceleration for 0.3 secondperiod with a 10% probability of exceedance in 50 years. All ofthe maps were prepared by combining hazard derived from spatially-smoothed historic seismicity with hazard from fault-specific sources.The acceleration values contoured are the random horizontal component.The reference site condition is firm rock, defined as having an averageshear-wave velocity of 760 m/sec in the top 30 meters corresponding tothe boundary between NEHRP site classes B and C. This data set represents the results of calculations of hazard curvesfor a grid of points with a spacing of 0.1 degrees in latitude andlongitude. The grid of points were contoured to produce the finalrepresentation of the seismic-hazard.